Checking presence of excess volatility in forecasting volatility of a set of market indexes through an empirical comparison of three GARCH models - boutabba, islem ahmed (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Classical financial theory is based on Efficient Market Hypothesis (EMH). Several researchers likeSchiller (1981) (1990), Le Roy and Porter (1980) have extensively argued for the invalidity of EMH. Volatility excess has been detected and highlighted by many researchers; however it has not been explained very well by EMH. For this reason, we conducted an empirical study to identify the variable characteristics of volatility by comparing three GARCH models (GARCH, E-GARCH and GRJ-GARCH) over five different market indexes to examine prediction of returns volatility.This comparison led us to detect several volatility characteristics like volatility clustering and leverage effect. This change in volatility regime is an irrefutable proof of the presence of volatility excess.Given the inability of classical financial theory in explaining volatility excess, researchers started to focus on behavioural finance (Barret and Saphister (1996)).